Generalized Pustular Psoriasis in Childhood: A Rare Case - Asnawi, Vella; Maulida, Mimi; Earlia, Nanda; Hidayati, Arie; Ismida, Fitri Dewi; Liana, Mahda Rizki; Maghfirah, Karamina; Bulqiah, Mikyal (Berkala Ilmu Kesehatan Kulit dan Kelamin, 2023)
Background: Generalized pustular psoriasis (GPP) rarely occurs under 10 years of age. GPP is typically characterized by an eruption of generalized pustules accompanied by systemic symptoms such as fever for several days, malaise, and anorexia. Pustules are sterile, with a size of 2-3 mm, and spread over the trunk and extremities. This disease can be life-threatening; therefore, optimal therapy is required. Purpose: to report a rare case of GPP in childhood. Case: A 4-year-old girl with complaints of widespread red patches that spread to her neck, back, and hands, with red patches turning into streaks that are partially pus-filled and itchy. In almost all parts of the body, skin abnormalities were seen in the form of generalized erythematous plaques, well-defined borders, multiple pustules on the edges, and some plaques covered by thick scales and crusts. In the calculation of body surface area (BSA), the result is 44%, and in the calculation of generalized pustular psoriasis area and severity index (GPPASI), the result is 21.30. The patient was treated with combination topical therapy of 3% salicylic acid, desoximethasone cream 0.25%, momethasone cream 0.1% vaseline albume as emollients, and coal tar. Significant improvement was seen after 1 month of therapy. Discussion: GPP in children is a rare case. GPP is idiopathic and can be life-threatening. Until now, there has been no standard therapy that is considered the most effective and safe for children. Topical therapy may be an option.